Major families of multiresistant plasmids from geographically and epidemiologically diverse staphylococci - Shearer, J.; Wireman, J.; Hostetler, J.; Forberger, H.; Borman, J.; Gill, J.; Sanchez, S.; Mankin, A.; LaMarre, J.; Lindsay, J.; Bayles, K.; Nicholson, A.; et al. (Genetics Society of America, 2011)
Staphylococci are increasingly aggressive human pathogens suggesting that active evolution is spreading novel virulence and resistance phenotypes. Large staphylococcal plasmids commonly carry antibiotic resistances and virulence loci, but relatively few have been completely sequenced. We determined the plasmid content of 280 staphylococci isolated in diverse geographical regions from the 1940s to the 2000s and found that 79% of strains carried at least one large plasmid >20 kb and that 75% of these large plasmids were 20–30 kb. Using restriction fragment length polymorphism (RFLP) analysis, we grouped 43% of all large plasmids into three major families, showing remarkably conserved intercontinental spread of multiresistant staphylococcal plasmids over seven decades. In total, we sequenced 93 complete and 57 partial staphylococcal plasmids ranging in size from 1.3 kb to 64.9 kb, tripling the number of complete sequences for staphylococcal plasmids >20 kb in the NCBI RefSeq database. These plasmids typically carried multiple antimicrobial and metal resistances and virulence genes, transposases and recombinases. Remarkably, plasmids within each of the three main families were >98% identical, apart from insertions and deletions, despite being isolated from strains decades apart and on different continents. This suggests enormous selective pressure has optimized the content of certain plasmids despite their large size and complex organization.